Impact of Bacteriophage Supplementation on Laying Hens' Egg Quality and Gut Microbiota - Mundrathi, Harika; Kumar Babu, Laxman; Kumar Panda, Arun; Panigrahi, Bhagirathi; Kumar Mishra, Sumanth (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study investigated the effect of bacteriophage supplementation on egg quality and gut microflora in laying hens. One hundred and  twenty Rhode Island Red laying hens were chosen at random. In a completely randomised design, they were split up into five groups  of 24, each with three replicates of eight, and were treated as T1 group (Control), that received a diet supplemented with no antibiotics  or bacteriophages; T2 group, received a diet supplemented with antibiotics (Oxytetracycline @ 50 g/quintal of feed),while T3, T4, and  T5 groups received bacteriophages at varying concentrations of 0.20 mL, 0.25 mL and 0.30 mL per litre of drinking water, respectively. The  addition of either antibiotic or bacteriophage did not affect any of the egg quality metrics (albumen percentage, yolk percentage, eggshell  percentage, egg shape index, Haugh unit, and eggshell thickness). In comparison to the control and antibiotic-supplemented groups,  bacteriophage supplementation significantly (p
Keywords: Albumen; Anti-microbial resistance; Bacteriophage; Gut microbiota; Poultry